La inconstitucionalidad de la orden de apremio personal a los adultos mayores como obligados subsidiarios. - Sánchez Yaguachi, Alex Darío (2014)
The present research , I've done in foundation having studied a problem that lies in the implementation of food to adults and seniors forced subsidiary without proper constitutional argument pensions; ignorance or lack of knowledge on the concept and application of the balancing exercise of fundamental rights efectivizan rights of vulnerable people in society .